Novel Au Carbene Complexes as Promising Multi-Target Agents in Breast Cancer Treatment - Jessica Ceramella; Annaluisa Mariconda; Marco Sirignano; Domenico Iacopetta; Camillo Rosano; Alessia Catalano; Carmela Saturnino; Maria Stefania Sinicropi; Pasquale Longo (MDPI AG, 2022)
Over the past decade, metal complexes based on N-heterocyclic carbenes (NHCs) have attracted great attention due to their wide and exciting applications in material sciences and medicinal chemistry. In particular, the gold-based complexes are the focus of research efforts for the development of new anticancer compounds. Literature data and recent results, obtained by our research group, reported the design, the synthesis and the good anticancer activity of some silver and gold complexes with NHC ligands. In particular, some of these complexes were active towards some breast cancer cell lines. Considering this evidence, here we report some new Au-NHC complexes prepared in order to improve solubility and biological activity. Among them, the compounds 1 and 6 showed an interesting anticancer activity towards the breast cancer MDA-MB-231 and MCF-7 cell lines, respectively. In addition, in vitro and in silico studies demonstrated that they were able to inhibit the activity of the human topoisomerases I and II and the actin polymerization reaction. Moreover, a downregulation of vimentin expression and a reduced translocation of NF-kB into the nucleus was observed. The interference with these vital cell structures induced breast cancer cells' death by triggering the extrinsic apoptotic pathway.